Peran Cruelty Free International (CFI) Dalam Menangani Kasus Animal Testing di Jerman - Maesarah, Lis; Wahyu R., Frentika (Department of International Relations, Universitas Mulawarman, 2024)
The case of animal testing violations in Germany was uncovered through an investigation conducted by Cruelty Free International (CFI). The high number of animal testing violations in Germany has been increasing annually. CFI, as an international organization dedicated to animal welfare, initiated its investigation in 2015 into Germany's largest private laboratory, LPT. In 2020, CFI successfully persuaded LPT to cease using animals as test subjects, in line with CFI's principles.